The relationship between teacher burnout and student motivation. (31st July 2015) - Shen, Bo; McCaughtry, Nate; Martin, Jeffrey; Garn, Alex; Kulik, Noel; Fahlman, Mariane
Abstract : Background: Teacher burnout is regarded as a serious problem in school settings. To date, studies on teachers' stress and burnout have largely centred on teachers' own characteristics, socialization, and behaviours, but few have explored the connection between teachers' burnout and students' motivation via their own perceptions of teachers' behaviour and emotional well‐being. Aims: This study adopted Maslach et al .'s (2001, Annu. Rev. Psychol ., 52, 397) job burnout construct and self‐determination theory to investigate the relationships between teachers' burnout and students' autonomous motivation over one‐semester physical education classes. Sample: A total of 1, 302 high school students and their 33 physical education teachers in 20 high schools from two school districts in a major Midwest metropolitan area in the United States. The two school districts were demographically similar. Methods: Students and physical education teachers completed questionnaires assessing relevant psychological constructs. There were two time points for collecting students' data. One was at the beginning of a fall semester, and the other was at the end of that semester. Hierarchical linear modelling analyses were conducted. Results: It was revealed that teachers' emotional exhaustion was negatively related to students' perceived teacher autonomy support (TAS); in turn, there was a negative relationship between teachers' feeling of depersonalization and students' autonomous motivation development even when controlling for inadequate TAS. Conclusion: The dimensions of teachers' burnout might play different roles in the transmission from teachers to students. Teachers' status of burnout is an important environmental factor associated with students' quality of motivation.